Dinamika Masyarakat Transmigrasi Rimbo Ilir Kabupaten Tebo Tahun 1978-2016 - Krismonita Sandi; Irhas Fansuri Mursal; Fatonah (Prodi Ilmu Sejarah, Jurusan Sejarah, Seni dan Arkeologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, bekerja sama dengan Masyarakat Sejarawan Indonesia, Jambi, 2021)
Rimbo Ilir transmigration settlement was opened for the first time in 1978. This transmigration area is a residential area for transmigrants originating from Wonogiri Regency. This study aims to determine the process of entering the transmigration community in Rimbo Ilir District, Tebo Regency, the dynamics of the transmigration community in Rimbo Ilir and the development of the socio-economic life of the Javanese transmigrant community in Rimbo Ilir District. This study used a historical research method consisting of four steps, namely collection of sources, source criticism, interpretation and historiography. Sources that are widely used in this study are oral sources because the perpetrator is still there and allows him to be interviewed. The results showed that the transmigrants who came were Bedol Desa transmigrants who came from Wonogiri Regency. The background of the arrival of the transmigrants was that their area was inundated by the construction of the Gajah Mungkur Reservoir and to improve economic life by opening new land. Since the arrival of the transmigrants, their socio-economic life has grown rapidly because of the rapid development of rubber plants and the price is quite expensive, the harvest period is relatively fast and the risk of loss is minimal, making the economic situation of the transmigration community gradually improved.